2007
DOI: 10.1038/sj.ejcn.1602787
|View full text |Cite
|
Sign up to set email alerts
|

Removing lactose from milk does not delay bowel function or harden stool consistency in lactose-tolerant women

Abstract: Objectives: To investigate whether removing lactose from milk delays bowel function in lactose-tolerant women. We also examined how well the participants' subjective evaluation of the stool consistency according to the Bristol Stool Form Scale correlated with values obtained by dry matter analysis and penetrometry. Subjects and methods: A randomized double-blind cross-over trial. Thirty-three lactose-tolerant women consumed, in random order, 800 ml of lactose-free or ordinary milk per day for 2 weeks, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…In the case of stool form, clinical trials still rely heavily on the BSS (6) to provide a guide for subject self-reporting of stool form. The BSS has been validated in several studies and found to be useful in the evaluation of stool hardness (15) and in rating individual stool type (16) but was less useful in determining Rome III stool form categories (16), and some users have shown difficulties classifying certain stool types correctly (17). However, there remain many challenges with asking the subject to use the BSS.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of stool form, clinical trials still rely heavily on the BSS (6) to provide a guide for subject self-reporting of stool form. The BSS has been validated in several studies and found to be useful in the evaluation of stool hardness (15) and in rating individual stool type (16) but was less useful in determining Rome III stool form categories (16), and some users have shown difficulties classifying certain stool types correctly (17). However, there remain many challenges with asking the subject to use the BSS.…”
Section: Discussionmentioning
confidence: 99%
“…In order that the stool models accurately represented the seven types on the BSFS and six intermediate types, 25 models were initially created with a range of water content (50–88%) based on experimental data . These were then evaluated by three experts in gastrointestinal research who independently selected the seven models that best represented the BSFS types (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Stool consistency is a central component in the description of normal or altered bowel habit. Stool consistency generally refers to the rheology or viscosity of the stool and is determined largely by stool water content . Rapid intestinal transit limits gastrointestinal water absorption leading to loose or liquid stools, whereas slow intestinal transit results in extensive water absorption leading to harder stools .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BSFS has been widely used in research and clinical settings and recommended by both the Rome Foundation for functional gastrointestinal disorders [24] and the United States' Food and Drug Administration [25]. It has been shown to correlate to gut transit time [26,27], as well as to stool hardness and dry matter [28]. Moreover, substantial validity and reliability have been demonstrated for the BSFS [29].…”
Section: Discussionmentioning
confidence: 99%